Promoting Upstanding Behavior in Youth: A Proposed Model. (August 2019) - Vera, Elizabeth; Hill, Lincoln; Daskalova, Plamena; Chander, Natasha; Galvin, Sarah; Boots, Tonya; Polanin, Megan
Despite what we have learned about the causes and consequences of bullying, efforts to reduce bullying through interventions to date have yielded modest results. Most bullying prevention efforts have targeted perpetrators and victims, ignoring the powerful role that observers play in maintaining cycles of bullying. This article presents literature from the fields of bystander behavior, empathy training, multicultural education, and ally/social justice orientation development; integrates relevant findings; and proposes a comprehensive model of upstanding behavior to inform prevention efforts. Through helping youth understand the value of being upstanders, there is a greater propensity for our schools and communities to become safer, more compassionate places that value the contributions of all members.